(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Hospital services are the amenities provided by a hospital both for the patients and the workforces. Periodical assessment of hospital service quality discovers the demands and needs thus ensuring the development of the institution. The aim of the study to find out the problems regarding hospital services and its solution. Materials and methods: This observational study was conducted among the health personnel of Chattogram Maa-O-Shishu Hospital from 01 July to 30 August 2019 and 01 January to 29 February 2020. Purposive sampling technique was followed to collect data from 100 randomly selected samples. They were interviewed with pretested questionnaire and data were managed manually. Results: Different findings were drawn. These are: Lack of work dedication, responsibility, loyalty and internal co-operation among the staff (60%). Lack of manpower including doctors, nursing staff, cleaners and few recruitments are not so experienced as to fulfill the demands of their duty (56%). The number of beds is less compared to the number of patients who need them e.g. ICU, CCU, NICU, Paediatric ICU Adult medicine ward, etc. Hence patients are referred outside (46%). Patient visiting hours and number of visitors not properly maintained. Visitors make noise, take food on patient’s bed and sometime physically assault employees when they are asked to obey rules (40%). However, overall job satisfaction of the respondents was 78%. Conclusion: Ascertaining the issues regarding the improvement of hospital services is mandatory. Quick detection and early solution would gain confidence by employees and beneficiary which would ultimately boost up the reputation of the hospital. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 41-44